Analisis Hubungan Ekspor, Pertumbuhan Ekonomi, dan Kesempatan Kerja Di Provinsi Bali : Pengujian Vector Auto Regression - Priyono, Dedi; Wirathi, I G.A.P. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 12, Desember 2016 (pp. 1347-1585), 2017)
Economic development can’t be separated from the role of human resources for its human resources or labor is an important factor to realize do the construction is running as expected and effectively. Employment opportunities can not be separated from economic growth while ertumbuhan economic driven by export. Based on it, research aims to understand relations causality a reciprocal between export, economic growth and job opportunities in bali province. This research using the kind of data sekuder to technique data analysis vector auto regressive (VAR). Trail phases namely the unit root, the lag steady, granger causality test, the var , the response , and variance decomposition .The results showed variable testing third there was no correlation causality ( relationships ) in bali province in the period this research. Testing var obtainable test results that export t-1 influenced exports and economic growth influenced petumbuhan t-1 economy. Testing last variance decomposition obtainable that export contribution towards economic growth much better compared to employment opportunities otherwise employment opportunities contribution better given by economic growth.
Keywords: Exports; economic growth; employment opportunities; VAR; Variance Decomposition